2007
DOI: 10.1051/0004-6361:20077086
|View full text |Cite
|
Sign up to set email alerts
|

The sedentary survey of extreme high-energy peaked BL Lacs

Abstract: Aims. The multi-frequency sedentary survey is a flux-limited, statistically well-defined sample of highly X-ray dominated (i.e., with a very high X-ray to radio flux ratio) BL Lacertae objects, which includes 150 sources. In this paper, the third of the series, we report the results of a dedicated optical spectroscopy campaign that, together with results from other independent optical follow-up programs, led to the spectroscopic identification of all sources in the sample. Methods. We carried out a systematic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(80 citation statements)
references
References 34 publications
4
72
3
1
Order By: Relevance
“…7, in infrared light, the host galaxy dominates the AGN emission. This is consistent with the optical spectrum measured by Piranomonte et al (2007) when evaluating the redshift of the source (see Figs. 2 and A.1 in their paper) and with the fact that the variability amplitude in the B band is significantly larger than that in the R band.…”
Section: Ssc Modelling Of the Sedsupporting
confidence: 90%
See 1 more Smart Citation
“…7, in infrared light, the host galaxy dominates the AGN emission. This is consistent with the optical spectrum measured by Piranomonte et al (2007) when evaluating the redshift of the source (see Figs. 2 and A.1 in their paper) and with the fact that the variability amplitude in the B band is significantly larger than that in the R band.…”
Section: Ssc Modelling Of the Sedsupporting
confidence: 90%
“…1RXS J101015.9−311909 belongs to the ROSAT All Sky Survey Bright Source Catalog (RASS/BSC) of soft (0.1−2 keV) X-ray sources (Voges et al 1999), with a flux of 2.9 × 10 −11 erg cm −2 s −1 . It is located at a position of (α J2000 , δ J2000 ) = (10 h 10 m 15.9 s , −31 • 19 09 ) 1 and has a redshift of z = 0.14 (see Piranomonte et al 2007, for both measurements). The source is present in the NRAO VLA Sky Survey (NVSS) catalogue of radio sources at 1.4 GHz (Condon et al 1998), which lists its flux density as 73.5 ± 2.7 mJy.…”
Section: Introductionmentioning
confidence: 99%
“…Studies performed by Massaro et al (2011b) andD'Abrusco et al (2012), based on data from the Wide-field Infrared Survey Explorer (WISE, Wright et al 2010), have shown that blazars tend to concentrate in a distinct region of the IR colour-colour diagram, known as the WISE blazar strip. For this purpose, we used the latest version of the WISE catalogue (ALLWISE), including 747 million objects, and the complete sample of about 150 HSPs from the Sedentary Survey (Giommi et al 1999;Piranomonte et al 2007), which represents well, both in terms of overall SED shape and fluxes, the type of extreme blazars that we want to select in this paper. The Sedentary Survey selects high Galactic latitude (|b| > 20 • ) sources characterised by a very high X-ray to radio flux ratio ( f x / f r ≥ 3 × 10 −10 erg cm −2 s −1 Jy −1 ) by means of a multifrequency method.…”
Section: Building a Large Sample Of Hsp Blazarsmentioning
confidence: 99%
“…Giommi et al 2012a). Following the work of Landt et al (2002) and Piranomonte et al (2007), we assume a giant elliptical host galaxy to be present in every blazar that would leave no imprint on the optical band if the total observed flux f obs exceeds the galaxy flux f ell by at least a factor of 10. Therefore, a lack of redshift allows us to set a lower limit based on the apparent magnitude m in the optical band.…”
Section: Lower Limits On Redshiftsmentioning
confidence: 99%
“…Following attempts (Wei et al 1999;Bauer et al 2000;Caccianiga et al 2002;Piranomonte et al 2007) have all failed to detect any spectral features and the redshift remains unknown. Piranomonte et al (2007) derived a lower limit z > 0.193 based on the absence of host galaxy features in the spectrum. In the only imaging attempt so far, Nilsson et al (2003) did not detect the host galaxy in a 1200 s R-band exposure.…”
Section: Introductionmentioning
confidence: 99%